Predictors of Hand-Washing Practices at Critical Times Among Mothers of Under-5 Years Old Children in Rural Setting of Gedeo Zone, Southern Ethiopia - Ashenafi Agaro; Habtamu Endashaw Hareru; Temesgen Muche; Daniel Sisay W/tsadik; Zemachu Ashuro; Belay Negassa; Mehret Tesfu Legesse; Abdene Weya Kaso; Wagaye Alemu; Addisu Alemayehu Gube; Mekonnen Birhanie Aregu; Negasa Eshete Soboksa (SAGE Publishing, 2022)
Background: Various communicable and infectious diseases could be contained by proper hand washing leading to a reduction in mortality and morbidity of children. Objective: To assess predictors of hand-washing practices at critical times among mothers of under 5 years old children in rural setting of Gedeo zone, Southern Ethiopia. Method: An institutional-based cross-sectional survey was conducted among 422 women with children under the age of 5 attended the Dilla Zuria health facility and were chosen using a systematic sampling method. Data was gathered using pre-tested interview-administered structured questionnaires. Data was entered into EPI info version 17 and analyzed using SPSS version 25. Binary logistic regression was employed to identify the association between dependent and independent variables. Finally, for variables with a P  < .05 in multivariable analysis, adjusted odds ratio (AOR) with a 95% confidence interval (CI) was determined and interpreted. Results: The hand washing practice of mothers at critical times was 44.9% [95% CI: 40.1, 49.7%]. The pertinent predictors were favorable attitude [AOR = 7.77, 95% CI: 4.56, 10.37], availability of water source near the household [AOR = 5.31, 95% CI: 3.56, 10.37], and constant availability of soaps at household [AOR = 2.32, 95% CI: 1.33, 6.70]. Conclusion: In our study, hand-washing practices at critical times was low. The pertinent predictors were attitude, the presence of a water source near the household, and the presence of soap. Therefore, it is advised to encourage domestic hygiene education to improve mothers' attitudes and to increase the availability of water and soap close to the household to promote handwashing with soap and water at critical times.